2020
DOI: 10.1101/2020.11.06.371617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistence of SARS-CoV-2 specific B- and T-cell responses in convalescent COVID-19 patients 6-8 months after the infection

Abstract: Background: The longevity of the immune response against SARS-CoV-2 is currently debated. We thus profiled the serum anti-SARS-CoV-2 antibody levels and virus specific memory B- and T-cell responses over time in convalescent COVID-19 patients. Methods: A cohort of COVID-19 patients from the Lombardy region in Italy who experienced mild to critical disease and Swedish volunteers with mild symptoms, were tested for the presence of elevated anti-spike and anti-receptor binding domain antibody levels over a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
85
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(99 citation statements)
references
References 47 publications
(69 reference statements)
12
85
0
2
Order By: Relevance
“…However, this evidence derives from small, observational studies conducted on samples taken from participants at varying time points, and with selection criteria rarely described. The longevity of this T cell immunity and the degree of protection it provides remains unclear, though recent pre-print papers from studies with longer follow-up report durability of virus-specific T cells for as long as 6–8 months following infection [ 83 , 84 ]. Recent epidemiological and animal model evidence hints at the protective function of T cells [ 85 , 86 ], and is supported by identification of detectable virus-specific T cell responses in seronegative COVID-19 convalescents [ 87 89 ], and in uninfected individuals with known exposure [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this evidence derives from small, observational studies conducted on samples taken from participants at varying time points, and with selection criteria rarely described. The longevity of this T cell immunity and the degree of protection it provides remains unclear, though recent pre-print papers from studies with longer follow-up report durability of virus-specific T cells for as long as 6–8 months following infection [ 83 , 84 ]. Recent epidemiological and animal model evidence hints at the protective function of T cells [ 85 , 86 ], and is supported by identification of detectable virus-specific T cell responses in seronegative COVID-19 convalescents [ 87 89 ], and in uninfected individuals with known exposure [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…The receptor binding motif within the spike protein interacts with the ACE2 receptor and is a major target of antibody-mediated neutralization. Longitudinal and cross-sectional studies have estimated that antibodies to the spike protein can last for at least a year following infection (Anand et al, 2021; Dan et al, 2021; Pradenas et al, 2021; Sherina et al, 2021). The mRNA-1273 vaccine encodes the viral spike protein and elicits a potent neutralizing antibody response to SARS-CoV-2 that is durable for several months (Anderson et al, 2020; Jackson et al, 2020; Widge et al, 2021).…”
Section: Figurementioning
confidence: 99%
“…Recent studies have found that binding and neutralizing antibodies are maintained for at least eight months following SARS-CoV-2 infection (Dan et al, 2021; Pradenas et al, 2021; Sherina et al, 2021). To understand how antibody breadth is impacted during convalescence, we performed a longitudinal analysis of RBD binding and viral neutralization in 30 convalescent COVID-19 individuals across two longitudinally sampled timepoints through 8 months ( Supplementary Table 2 ).…”
Section: Figurementioning
confidence: 99%
“…Immune repertoire sequencing suggests the T-cell repertoire to decrease in early infection followed by an expansion in convalescent production phase, while the B-cell repertoire has isotype switching and clonal expansion [ 168 ]. These responses have been shown to last for 6–8 months [ 169 ], with further need for longitudinal follow up to determine the length of adaptive resistance to the virus. This immune repertoire sequencing combined with single-cell RNAseq has been pivotal in the rapid determination of neutralizing antibodies to the SARS-CoV-2 virus [ 170 ], opening the door for the rapid generation of viral neutralizing drugs.…”
Section: Covid-19 Clinical Course and Pathologymentioning
confidence: 99%